(untitled) (International Journal of Food and Nutritional Sciences, 2022)
China’s perilous rise has led to its securitization by its neighboring states, particularly given its precarious maritime claims in the strategic waters of the Indo-Pacific. Extra-regional states, too, fear the threatened rules-based international order in the region, as more than half of the world’s maritime trade is conducted through these waters. Such a development in the region has allowed Germany and Japan to strengthen their strategic partnerships in the Indo-Pacific. The securitization of China, coupled with Germany and Japan’s common interests in safeguarding rules-based international order and deterring unilateral changes to the status quo, contributed to the emergence of this engagement. Moreover, the growing engagement provides Southeast Asian states a hedging option as China’s assertion of its territorial claims increases. This paper uses securitization theory to analyze the emerging German-Japanese cooperation in the Indo-Pacific. Germany’s policy guidelines for the Indo-Pacific region and Japan’s Free and Open Indo-Pacific (FOIP) strategy have been analyzed to show the emergence of German Japanese cooperation.